Corporate Social Responsibility Optimization as Collaborative Funding Innovation to Support Sustainable Development - Lindawati Lindawati; Yudhanty Parama Sany; Sak Khie; Iwan Syahrul Anwar; Dewi Listiorini (Universitas Negeri Malang, 2024)
During the pandemic, development progress is hindered by budget constraints. Meanwhile, the business sector's contribution to development is minimal and charitable, with no significant impact. To address this issue, a program called